Effect of protein restriction of bovine dams during late gestation on offspring postnatal growth, glucose-insulin metabolism and IGF-1 concentration - Maresca, Sebastian; Lopez Valiente, Sebastian; Rodriguez, Alejandro Martin; Long, Nathan M.; Pavan, Enrique; Quintans, Graciela I. (2018)
The objective of this study was determine whether the amount of protein provided to cows during late gestation would affect postnatal growth and lead to changes on glucose, insulin and insulin-like growth factor concentrations. At 134 d prepartum, 68 multiparous Angus cows were blocked by BW and expected calving date and randomly assigned to low protein level (LP, 6% CP) or high protein level (HP, 12% CP) and were allotted in 12 pens per treatment. At calving, cows were managed together on improved pastures until weaning. Calves were weighed and body measurements were recorded at birth. Blood samples were taken at birth and each 30 d until weaning at 180 d of age. Body weight at birth on HP progeny tended to be great than LP progeny (P = 0.06). At birth, calves from LP dams had greater head circumference (P 〈 0.01), heart girth (P = 0.01) and cannon bone circumference (P = 0.02). However, head circumference /birth BW ratio (P = 0.04), heart girth /birth BW ratio (P = 0.01), body length /birth BW ratio (P = 0.05) and height /birth BW ratio (P = 0.01) was greater on LP calves. Body mass index was greater in HP calves (P = 0.04). No differences were found on BW of calves at weaning, adjusted 205d BW and ADG during lactation (P 〉 0.10). Glucose concentrations were greater on LP calves than HP calves from birth to weaning (81.0 ± 1.5 vs. 76.4 ± 1.2 mg/dl; P 〈 0.001) without any change in insulin concentrations during preweaning growth (LP = 1.61 ± 0.04 ng/ml; HP = 1.61 ± 0.04 ng/ml; P 〉 0.10). Insulin-like growth factor concentrations was less on LP calves at birth (P 〈 0.05) and similar to HP calves during postnatal growth (P 〉 0.10). These data demonstrate that low protein during late gestation in bovine dams may affect fetal growth with proportional increasing of head circumference and low body mass index. Level of protein compromised glucose regulation in early life and affected the IGF-I concentration of newborn calves.